MOTIF MENUHI INFORMASI LEWAT SITUS www.juventusclubindonesia.com DENGAN KEPUASAN ANGGOTA JUVENTUS CLUB INDONESIA - Fauzi, Rizky (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
Website nowadays has become a means of communication for everyone , thats what the fan community Juventus( Juventus Club Indonesia ) . Www.juventusclubindonesia.com site by the author as research object because www.juventusclubindonesia.com site presents useful information for members of the Juventus Club Indonesia , the authorsare interested to raise permasalan about whether members club Juventus Indonesia Bekasi chapter satisfiedwith the presentation of information on the website www . juventusclubindonesia.com . In this study the authorsassign members Juventus Club Indonesia Bekasi chapter of the study population . The purpose of this study soughtto determine satisfaction and satisfaction obtained for members of the Juventus Club Indonesia Bekasi chapterwww.juventusclubindonesia.com accessing the site .In this study, the theory used is the Uses and Gratification theory , this research is descriptive quantitative , Populationtaken juventus club is a member of Indonesia Bekasi chapter . The sample used berdarkan Taro Yamaneformula . Sampling technique using Simple Random Sampling . Research data that has been collected throughquestionnaires answered by the sample , each answer was given a score based on the Likert scale . In this study ,researchers used quantitative analysis techniques with Descriptive type